Understanding and application of restoring endodontically treated teeth among dentists of Islamabad and Rawalpindi - a twin city survey - Rabia Qamar; Seemi Tanvir; Quratulain Khan; Nouman Noor; Sadaf Humayoun; Ayesha Fazal (Journal of University Medical & Dental College, 2023)
BACKGROUND & OBJECTIVE: Endodontically treated teeth undergo loss of tooth structure resulting in increased fracture susceptibility as compared to unrestored vital teeth. The final restoration following the root canal treatment is of paramount importance. This study aimed to determine current concepts, opinions, and techniques used for restoration of Endodontically Treated Teeth among dentists of Islamabad and Rawalpindi and compare their knowledge with their clinical practice in order to determine the gap between their understanding and application. METHODOLOGY: A cross-sectional study, conducted in Rawal Institute of Health Sciences, Islamabad from February-June 2022 after ethical approval. Convenience sampling technique was used. About 235 dentists including house officers, general dentists, postgraduate trainees and consultants of Endodontics of Islamabad/Rawalpindi participated. Data was collected by structured questionnaire widely accepted with Cronbach’s alpha of 0.75, through electronic media. Its first part included demographics while second part included questions regarding understanding and practice of endodontically treated teeth restoration. Statistical analysis was done by using SPSS 2, chi-square test and fisher’s exact test were applied. RESULTS: Mean age of study participants was 29.0±4.54 years. Out of 235 participants, 76(32.3%) were males and 159(67.75%) were females. The responses regarding technical management of endodontically treated teeth showed significant difference with p-value≤0.001 in the understanding and applications of general dental practitioners and endodontists. CONCLUSION: Significant difference was found among dentists regarding their understanding and practice of restoring endodontically treated teeth.